Risk of Invasive Anal Cancer in HIV-Infected Patients With High-Grade Anal Dysplasia: A Population-Based Cohort Study. Issue 8 (August 2019) - Arens, Yotam; Gaisa, Michael; Goldstone, Stephen E.; Liu, Yuxin; Wisnivesky, Juan; Sigel, Carlie S.; Swartz, Talia H.; Sigel, Keith
Abstract : BACKGROUND: The progression rate and predictors of anal dysplastic lesions to squamous cell carcinoma of the anus remain unclear. Characterizing these parameters may help refine anal cancer screening guidelines. OBJECTIVE: This study aimed to determine the rate of progression of high-grade anal dysplasia to invasive carcinoma in HIV-infected persons. DESIGN: Using the Surveillance, Epidemiology, and End Results database linked to Medicare claims from 2000 to 2011, we identified HIV-infected subjects with incident anal intraepithelial neoplasia III. To estimate the rate of progression of anal intraepithelial neoplasia III to invasive cancer, we calculated the cumulative incidence of anal cancer in this cohort. We then fitted Poisson models to evaluate the potential risk factors for incident anal cancer. SETTINGS: This is a population-based study. PATIENTS: Included were 592 HIV-infected subjects with incident anal intraepithelial neoplasia III. MAIN OUTCOME MEASURES: The primary outcome measured was incident squamous cell carcinoma of the anus. RESULTS: Study subjects were largely male (95%) with a median age of 45.7 years. Within the median follow-up period of 69 months, 33 subjects progressed to anal cancer. The incidence of anal cancer was 1.2% (95% CI, 0.7%–2.5%) and 5.7% (95% CI, 4.0%–8.1%) at 1 and 5 years, following a diagnosis of anal intraepithelial neoplasia III. Risk of progression did not differ by anal intraepithelial neoplasia III treatment status. On unadjusted analysis, black race ( p = 0.02) and a history of anogenital condylomata ( p = 0.03) were associated with an increased risk of anal cancer incidence, whereas prior anal cytology screening was associated with a decreased risk ( p = 0.04). LIMITATIONS: The identification of some incident cancer episodes used surrogate measures. CONCLUSIONS: In our population-based cohort of HIV-infected subjects with long-term follow-up, the risk of progression from anal intraepithelial neoplasia III to anal squamous cell carcinoma was higher than reported in other studies and was not associated with the receipt of anal intraepithelial neoplasia III treatment. See Video Abstract at http://links.lww.com/DCR/A933 . Abstract : Supplemental Digital Content is available in the text.